The effects of unsaturated fatty acids on hepatic microsomal drug metabolism and cytochrome P-450 - Di Augustine, Richard P. (1969)
1. The effects of unsaturated fatty acids on drug-metabolizing enzymes in vitro were measured by using rat and rabbit hepatic 9000g supernatant fractions. 2. Unsaturated fatty acids inhibited the hepatic microsomal metabolism of `type I' drugs with inhibition increasing with unsaturation: arachidonic acid>linolenic acid>linoleic acid>oleic acid. Inhibition was independent of lipid peroxidation. Linoleic acid competitively inhibited the microsomal O-demethylation of p-nitroanisole and the N-demethylation of (+)-benzphetamine. 3. The hepatic microsomal metabolism of `type II' substrates, aniline and (−)-amphetamine, was not affected by unsaturated fatty acids. 4. The rate of reduction of p-nitrobenzoic acid and Neoprontosil was accelerated by unsaturated fatty acids. 5. Linoleic acid up to 3·5mm did not decelerate the generation of NADPH by rat liver soluble fraction, nor the activity of NADPH–cytochrome c reductase of rat liver microsomes. Hepatic microsomal NADPH oxidase activity was slightly enhanced by added linoleic acid. 6. No measurable disappearance of exogenously added linoleic acid occurred when this fatty acid was incubated with rat liver microsomes and an NADPH source. 7. The unsaturated fatty acids used in this study produced type I spectra when added to rat liver microsomes, and affected several microsomal enzyme activities in a manner characteristic of type I ligands.